The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1038/sj.leu.2401943
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression levels of methotrexate resistance-related proteins in childhood leukemia as determined by a standardized competitive template-based RT-PCR method

Abstract: Drug resistance of leukemic blasts is correlated to event-free survival and might be predicted by mRNA expression of drug resistance-related proteins. Methotrexate (MTX) is an important component in the treatment of childhood leukemia. Mechanisms of MTX resistance include (1) decreased transport via the reduced folate carrier (RFC), (2) altered levels of target enzymes, eg dihydrofolate reductase (DHFR) and thymidylate synthase (TS), (3) decreased ratio of folylpolyglutamate synthetase (FPGS)/folylpolyglutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 48 publications
3
55
0
Order By: Relevance
“…The principles have been described in detail elsewhere (Willey et al, 1998;Rots et al, 2000;Crawford et al, 2001).…”
Section: Competitive Template Rt -Pcr To Determine Tp Mrna Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…The principles have been described in detail elsewhere (Willey et al, 1998;Rots et al, 2000;Crawford et al, 2001).…”
Section: Competitive Template Rt -Pcr To Determine Tp Mrna Expressionmentioning
confidence: 99%
“…RNA was extracted from 5 Â 10 6 cells by the RNAzol TM method, checked for DNA contamination and reverse transcribed by random hexamers as described by the manufacturer with minimal modifications (Rots et al, 2000). Competitive templates were designed for b-actin (Rots et al, 2000) and TP, using the primer sets shown in Table 1.…”
Section: Competitive Template Rt -Pcr To Determine Tp Mrna Expressionmentioning
confidence: 99%
See 3 more Smart Citations